2018
DOI: 10.1111/ctr.13195
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in kidney transplant waitlist appearance in Chicago: Is it race or place?

Abstract: Consistent with national data, African Americans in Chicago have a lower likelihood of waitlisting than whites. This disparity is explained in part by neighborhood poverty, which impacts the majority of African American ESRD patients in Chicago.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Reasons for these differences likely include both genetic predisposition as well as a long-term consequence of structural racism ( Beydoun et al, 2017 ; Parsa et al, 2013 ). Previous studies have observed that residence in predominantly Black neighborhoods is associated with lower rates of transplantation wait-listing ( Arriola, 2017 ; Peng et al, 2018 ). However, less is understood about the relationship of Hispanic ethnicity and CKD, at both an individual and neighborhood level.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for these differences likely include both genetic predisposition as well as a long-term consequence of structural racism ( Beydoun et al, 2017 ; Parsa et al, 2013 ). Previous studies have observed that residence in predominantly Black neighborhoods is associated with lower rates of transplantation wait-listing ( Arriola, 2017 ; Peng et al, 2018 ). However, less is understood about the relationship of Hispanic ethnicity and CKD, at both an individual and neighborhood level.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 While more difficult to quantify given that referral and listing rates are not tracked, evidence suggests inequities in access to kidney transplant start prior to listing as well, with factors such as gender, race, ethnicity, socioeconomic status, and health literacy all affecting the likelihood that a patient referred for transplant will subsequently get listed and transplanted. 24 26…”
Section: Discussionmentioning
confidence: 99%
“…In a study of United States Renal Data System (USRDS) data, Kucirka et al (2012) found that people were less likely to be listed if they were uninsured, African American or female. A more recent analysis of USRDS data has confirmed that people were less likely to be listed for transplant if they were African American or from a poorer socioeconomic group (Peng et al 2018). United Kingdom Renal Registry data in 2018 found that women were less likely than men to be activated on the renal transplant waiting list within two years of starting dialysis, and different referral patterns between transplanting and non-transplanting units meant that people dialysing at non-transplanting units were less likely to be listed for a transplant (Taylor et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%